1997
DOI: 10.1093/hmg/6.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the SOX9 gene in campomelic dysplasia and autosomal sex reversal: lack of genotype/phenotype correlations

Abstract: It has previously been shown that, in the heterozygous state, mutations in the SOX9 gene cause campomelic dysplasia (CD) and the often associated autosomal XY sex reversal. In 12 CD patients, 10 novel mutations and one recurrent mutation were characterized in one SOX9 allele each, and in one case, no mutation was found. Four missense mutations are all located within the high mobility group (HMG) domain. They either reduce or abolish the DNA-binding ability of the mutant SOX9 proteins. Among the five nonsense a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
146
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(155 citation statements)
references
References 28 publications
8
146
0
1
Order By: Relevance
“…The SOX9 nonsense mutation p.Y440* is recurrently seen in patients with acampomelic campomelic dysplasia (MIM114290) [34][35][36] , a severe form of skeletal dysplasia. Variable survival time of patients with this same mutation and lack of clear genotype-phenotype correlation among patients suggest that genetic modifiers that affect phenotypic variability may exist.…”
Section: A R T I C L E Smentioning
confidence: 99%
“…The SOX9 nonsense mutation p.Y440* is recurrently seen in patients with acampomelic campomelic dysplasia (MIM114290) [34][35][36] , a severe form of skeletal dysplasia. Variable survival time of patients with this same mutation and lack of clear genotype-phenotype correlation among patients suggest that genetic modifiers that affect phenotypic variability may exist.…”
Section: A R T I C L E Smentioning
confidence: 99%
“…Known SOX9 mutations include various missense substitutions in the high‐mobility group or dimerization domains, as well as several nonsense, frameshift, and splice‐site mutations widely distributed in the coding region (Meyer et al. 1997; Bernard et al. 2003; Harley et al.…”
Section: Introductionmentioning
confidence: 99%
“…SOX9 mutations also result in complete or partial gonadal dysgenesis in individuals with 46,XY karyotype (Meyer et al. 1997; Michel‐Calemard et al. 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is in this process that LSox5 has been most thoroughly studied. Mutations in SOX9 produce campomelic dysplasia, a syndrome that is often associated with autosomal XY sex reversal and involves the severe malformation of most cartilage-derived structures (Meyer et al, 1997). Furthermore, mouse chimeras containing Sox9 -/-embryonic stem cells inactivate early cartilage markers, including the Col2a1 gene (Bi et al, 1999), a phenomenon that is also observed in Sox5, Sox6 double mutant embryos (Smits et al, 2001).…”
Section: Introductionmentioning
confidence: 99%